AUDIT MANAJEMEN FUNGSI SUMBER DAYA MANUSIA PADAPT. LANDIPO NIAGA RAYA KENDARI - Ambarwati, Ambarwati (JURNAL AKUNTANSI, 2017)
ABSTRACTThe objective of this research was to carry out management audit to know and evaluate efectivity of human resources function of activity implementation function that throught recruitment and selection employee, working achievement evaluation for employee, and work force compensation employee at PT. Landipo Niaga Raya Kendari.The method that used by the researcher in this thesis descriptive analysis that give explanation about effectivinnes human resource of PT. Landipo Niaga Raya Kendari, then writer give some recommendations to management based on result of this thesis. To measure the effectivenness of human resource function, writer use questioner approach by giving two alternative of answer using Guttman scale.Research show that the function of human resource PT. Landipo Niaga Raya Kendari should increase management control of human resource function including in recruitment and selection employee, working achievement evaluation for employee, and work force compensation employee have not been run effectively. It is because the weakness of planning,, executing and controlling of human resource function system. Keywords : Management audit, and Human resources